2017
DOI: 10.48550/arxiv.1708.05293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong and weak single particle nonlocality induced by time-dependent boundary conditions

S. V. Mousavi,
A. Matzkin

Abstract: We investigate the issue of single particle nonlocality in a quantum system subjected to timedependent boundary conditions. We first prove that contrary to earlier claims, there is no strong nonlocality: a quantum state localized at the center of a well with infinitely high moving walls is not modified by the wall's motion. We then show the existence of a weak form of nonlocality: when a quantum state is extended over the well, the wall's motion induces a current density all over the box instantaneously. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This costs no work in principle because the wavefunction's value is 0. Further, it has been shown that motion of the wall through a region of zero wavefunction makes no change to the rest [18].…”
mentioning
confidence: 99%
“…This costs no work in principle because the wavefunction's value is 0. Further, it has been shown that motion of the wall through a region of zero wavefunction makes no change to the rest [18].…”
mentioning
confidence: 99%